"Und das ungeheure Bild der Landschaft...". The genesis of landscape understanding in the German-speaking regions. - Berr, Karsten; Kühne, Olaf (Springer VS, 2020)
The understanding of landscape in the German-speaking area has some similarities with the discussions of the topic in other European languages and scientific communities, but there are some specifics. These specifics can be found both in the common sense understanding of landscape and in the history of scientific conceptualization. Special features of the common sense understanding lie on the one hand in the medieval roots, a strong romantic charge and the strong connection between home and landscape. With regard to the scientific examination of landscape, there are specific fractions and discontinuities in the German-speaking world.
Keywords: Landschaft; Landschaftsbegriff; Landschaftsgeschichte; Heimatgefühl; Landschaftsplanung; Landschaftsarchitektur; Wissenschaftsdisziplin; Geographie